Spectral and pseudospectral functions of various dimensions for symmetric systems - Mogilevskii, V.I. (Український математичний вісник, 2016)
The main object of the paper is a symmetric system Jy′ − B(t)y = λ∆(t)y defined on an interval I = [a, b) with the regular endpoint a.